Ruptures in overhead ground wire — Transmission line 220 kV. (May 2018) - Arias Velásquez, Ricardo Manuel; Mejía Lara, Jennifer Vanessa
Abstract: The broken strand of overhead ground wire (OGW), which is mainly caused by lightning strikes or the vibration of OGW, can lead to serious damage to the power grid system. Power-line maintenance work is generally carried out by specialized workers under extra-high voltage live-line conditions which involve great risks and high labor intensity. If the OGW or OPGW are broken and they fall, this may cause a short-circuit fault of the power transmission lines. Besides this fault, in the event of OPGW breakage, communication interruption will also occur, causing significant damage to the communication system of the electric power utility and the public. Therefore, the melting and breaking characteristics of OGW strands must be clarified. In this research, a case study of a double simultaneous rupture in an OGW, it is analyzed in the Section 3, these simultaneous failures caused by lightning strikes were developed. The effects on the mechanical capacity and structural damaged is analyzed in the Section 4, a discussion has been considered in the Section 5. The calculation way will be also a good tool for developing a new OGW strand that is hard to melt and is broken by high-energy lightning strikes. Highlights: A double simultaneous rupture in an Overhead Ground Wires (OGW) has been analyzed. Lightning strikes effect on overhead lines. Sudden failure and fatigue has been compared.